CENTER LEARNING MODEL IN CHILDREN AGED 4-5 YEARS - Tri Ulya Wardati Qori'ah; Ruli Hafidah; Nurul Kusuma Dewi (Early Childhood Education and Development Journal, 2019)
This study aimed to describe the application of the beyond centers and circle time in children aged 4-5 years at Surakarta Islamic Consecrated Kindergarten. This problem was examined with a qualitative approach and the type of research case study. The research subjects involved were children, teachers, and parents. Data collected by researchers through interviews, observation and documentation. The data analysis technique used the Miles and Huberman analysis model. The technique of data validity testing was by source and technique triangulation. The results research of the application of the central learning model was carried out by organizing learning focusing on children in a circle using four types of scaffolding, namely playing environment, before playing, during play, and after playing. Bakti IX Islamic Kindergarten applied five school days, as well as one type of center every day, there are five centers that are implemented namely beam centers, centers of life skills, arts centers, preparation centers, and role-playing centers. The application of beyond centers and circle time can stimulate children to be able to optimize the six developmental fields of children. Learning media used ware APE and also the use of used goods.